Teacher's Perceptions towards Teaching Learning Practice at COVID Pandemic in Community School Nepal - Baraily, Khagendra; Sherpa, Dawa; Basnet, Hom Bahadur (Researcher: A Research Journal of Culture and Society, 2021)
This study employs the teaching learning practice adopted by student and teacher in the community school of rural areas in pandemic period. The world battle against corona virus disturbances every academic movement of institution. This study aims to dig out the student and teacher experiences from the community school and explore the perception about learning environment along with student connection indoor launched by the community school. In the philosophical standpoint, subjective reality is ontological stand and multiple realities are epistemological platform. Regarding to research design, hermeneutics phenomenology was chosen as qualitative approach. Purposively four teachers from community school were participated from Morag district, province no.1. The result showed that there is no effective means of learning mechanism in pandemic period. Most of the student's activity is deviated from the line of education because of various factors such as economy, family support, internet disturbance, and attitudinal barrier. The student's behavior was found to be beyond of education environment. The stakeholders of child education are found to be careless. Some of the community school in urban areas conducted their academic activity via internet but not sufficient. School in the rural areas completely stopped their activities due to various reasons. The rural municipality and school could not collaborate for running academic program. The students were not benefitted by education in the pandemic situation.